Designing an intuitive web application for drug discovery scientists. Issue 6 (June 2018) - Karamanis, Nikiforos; Pignatelli, Miguel; Carvalho-Silva, Denise; Rowland, Francis; Cham, Jennifer A.; Dunham, Ian
Graphical abstract: Highlights: Lean UX design helped our development team collaborate and empathize with users. User research and problem definition enabled us to understand user needs. Design workshops with users allowed us to come up with diverse designs. Getting feedback from a few users early and often ensured an intuitive application. Quantitative metrics supplement qualitative feedback in an iterative development process. Abstract : We discuss how we designed the Open Targets Platform (www.targetvalidation.org ), an intuitive application for bench scientists working in early drug discovery. To meet the needs of our users, we applied lean user experience (UX) design methods: we started engaging with users very early and carried out research, design and evaluation activities within an iterative development process. We also emphasize the collaborative nature of applying lean UX design, which we believe is a foundation for success in this and many other scientific projects.